Isotopic data and relative biomasses of ground-dwelling generalist predators in pure and mixed stands of European beech, Norway spruce and non-native Douglas fir - Benjamin Wildermuth; Riko Fardiansah; Dragan Matevski; Jing-Zhong Lu; Peter Kriegel; Stefan Scheu; Andreas Schuldt (PANGAEA, 2023)
The dataset contains calibrated isotopic data (?13C, ?15N) and relative biomasses of spiders and ground beetles, sampled in 2019 in Lower Saxony, Germany, within the RTG 2300 project "Enrichment of European beech forests with conifers". Arthropods were sampled with pitfall traps and identified to species level by Kriegel et al (2021) and Matevski and Schuldt (2023). Natural abundance isotopic ratios (δ13C, δ15N) were determined by the Centre for Stable Isotope Research Analysis at the University of Göttingen and thereafter calibrated with leaf litter isotopic ratios. Calibrated isotopic values (?) were used to calculate multidimenional isotopic metrics, which were compared between different stand types and regions. The stand types were Douglas fir, beech-Douglas fir, beech, beech-spruce and spruce.